2005
DOI: 10.1002/mus.20332
|View full text |Cite
|
Sign up to set email alerts
|

Lambert–Eaton myasthenic syndrome has a more progressive course in patients with lung cancer

Abstract: We studied whether a difference exists in the development of symptoms of the Lambert-Eaton myasthenic syndrome (LEMS) between patients with or without small cell lung cancer (SCLC). We assessed symptoms in 38 LEMS patients, 13 with SCLC, by interviewing them using a structured checklist, backed up by a review of their clinical records, and compared the frequency and time scale of symptoms during the course of LEMS. Bulbar (87%) and autonomic (95%) symptoms for the whole group were more common than reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 8 publications
4
26
0
3
Order By: Relevance
“…12,13 Our findings clearly support this rationale. In the seronegative group in which electrophysiological testing was needed for a definite diagnosis of LEMS, our study showed that the classic triad of abnormalities on RNS was rare, giving rise to a double difficulty in the diagnosis of LEMS.…”
Section: Discussionsupporting
confidence: 87%
“…12,13 Our findings clearly support this rationale. In the seronegative group in which electrophysiological testing was needed for a definite diagnosis of LEMS, our study showed that the classic triad of abnormalities on RNS was rare, giving rise to a double difficulty in the diagnosis of LEMS.…”
Section: Discussionsupporting
confidence: 87%
“…Bulbar symptoms may occur more frequently than previously reported [85] but are generally milder than with myasthenia gravis. Respiratory weakness can occur.…”
Section: Lemsmentioning
confidence: 59%
“…Deep tendon reflexes, especially those in the legs, are diminished or absent but may reappear after exercise. Autonomic features, especially dryness of the mouth, impotence, and mild/moderate ptosis, ultimately develop in 95% of patients [85][86][87]. In some patients, LEMS may develop in association with other PNS, including PCD and encephalomyelitis [50].…”
Section: Lemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening with CT-thorax or PET scans detected SCLC in 91 % of patients within 3 months after the diagnosis of LEMS (Titulaer et al 2008b). Specific symptoms do not distinguish between patients with and without underling SCLC, but LEMS associated with SCLC has a more progressive course (Wirtz et al 2005c). …”
Section: Small Cell Lung Cancermentioning
confidence: 98%